The Application of Acupressure Therapy in Handling Post-Chemotherapy Nausea and Vomiting - Novi Afrianti; Eri Riana Pertiwi (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Chemotherapy is an effective cancer treatment and works with the growth of cancer cells that develop and divide rapidly. Treatment with chemotherapy has side effects that are not small, one of which causes nausea, which affects nutritional intake. One method to deal with nausea and vomiting in chemotherapy patients is by acupressure therapy at point P6 above in the face of hands and St36 below the knee. The purpose of this study is to study the effect of acupressure therapy in handling nutritional problems in chemotherapy patients. This research is a Quasy Experiment study using nonequivalent design control group. The sample in this study amounted to 60 people who were divided into 30 people in the control group and 30 people in the intervention group. The intervention group received acupressure therapy 3 times a day, 25 minutes before chemotherapy, 6 and 12 hours after chemotherapy, while the control group received only standard therapy. The data collection of this research was used observation and interviews, and data analysis used the T test. The results showed the frequency of nausea releasing control group patients before releasing chemotherapy was dominant in the moderate category (50%) to severe (40%) after 24 hours without receiving chemotherapy, while the intervention group before giving dominant therapy at that time (53.3%) became Mild 53.3%) after being given acupressure. And from the t test results also obtained an alpha value of 0,000 which means there is a relationship between giving acupressure with decreasing frequency of nausea throwing at patients who are trying chemotherapy.